High SARS-CoV-2 IgG/IGM seroprevalence in asymptomatic Congolese in Brazzaville, the Republic of Congo. (May 2021) - Batchi-Bouyou, Armel Landry; Lobaloba Ingoba, Line; Ndounga, Matthieu; Vouvoungui, Jeannhey Christevy; Mfoutou Mapanguy, Claujens Chastel; Boumpoutou, Kamal Rauchelvy; Ntoumi, Francine
Highlights: COVID-19 infection from April to July 2020 in Brazzaville. Seroprevalence using two rapid diagnostic tests. IgG and IgM seroprevalence higher in Congolese women. 7.4% of RT-PCR positive asymptomatic Congolese adults. 15% of seroconverted Congolese adults. Abstract: Introduction: The Republic of the Congo detected its first case of coronavirus disease 2019 (COVID-19) on March 14, 2020, and within several weeks, the country had introduced protective measures that were still in force in July 2020. Over the course of time, the progression in the number of clinical cases has appeared to be lower than expected, although reverse transcription polymerase chain reaction (RT-PCR) testing has been somewhat limited. In order to evaluate the incidence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) within the Congolese population, a seroprevalence study was conducted on healthy individuals from different districts of Brazzaville who were willing to know their COVID-19 infection status. Methods: Oropharyngeal swab and blood samples were collected from 754 healthy volunteers between April 2020 and July 2020. The samples were analyzed for SARS-CoV-2 using a qualitative RT-PCR assay, and Immunoglobulin G (IgG) and Immunoglobulin M (IgM) antibodies were detected using two different rapid tests. Results: A total of 56 participants (7.4%) tested positive for SARS-CoV-2. The remaining 698 participants (92.6%) had negative RT-PCR results; of these, 117 were found to have anti-SARS-CoV-2 antibodies using serological tests. For these RT-PCR-negative subjects, the seroprevalence of IgG and IgM was found to increase over time: from 1.7% and 2.5% in April, up to 14.2% and 17.6% in July, respectively. In April 2020, 5% of the women were found to have IgG or IgM antibodies, whereas the antibodies were not detected in any of the men. The seroprevalence in RT-PCR negative subjects was significantly higher in women within IgG ( P = 0.012 ) and IgM ( P = 0.045 ) over the first three months. Conclusion: The proportion of the population who seroconvert over the course of the first wave is an important data to predict the risk of future COVID-19 waves and this will facilitate the efficient use of limited resources in a low income country like the Republic of the Congo.